Multidimensional Morse/Long-Range Potential Energy Surface and Predicted Rotational Spectra of the CH4–N2 Complex - Zhang, Xiao-Long; Li, Hui (The journal of physical chemistry. A, Molecules, spectroscopy, kinetics, environment, & general theory, 2025)
A five-dimensional intermolecular potential energy surface (PES) was developed for the CH4–N2 complex with methane fixed at its experimental equilibrium geometry. Intermolecular potential energies were calculated using the explicitly correlated coupled-cluster [CCSD(T)-F12] approach and the augmented correlation-consistent aug-cc-pVTZ basis set. A multidimensional Morse/long-range function was fitted to 49,385 ab initio points, yielding an analytic PES with a root-mean-square deviation of 0.441 cm–1. Rovibrational levels and corresponding wave functions were determined using a discrete variable representation and angular finite basis representation method in conjunction with the Lanczos algorithm. Furthermore, rotational transition frequencies for the CH4–N2 complex were predicted for the first time. The cross second virial coefficient for CH4–N2 was computed to assess the PES, showing reasonable agreement with the existing experimental data.